Apparent Diffusion Coefficient (ADC) Value on Magnetic Resonance Imaging (MRI) in Determining Breast Cancer and Determining Breast Cancer With Locally Advanced Expansion - I Gusti Agung Putra Mahautama; Firman Parulian Sitanggang; Elysanti Dwi Martadiani; I Gde Raka Widiana (Green Publisher Indonesia, 2025)
Breast cancer is the most common malignancy in women and a leading cause of cancer-related deaths in Indonesia. Early detection of the locally advanced stage is crucial for therapy selection and prognosis. This study evaluates the diagnostic value of the Apparent Diffusion Coefficient (ADC) from diffusion-weighted MRI (DWI) in detecting breast cancer and assessing local advancement. A retrospective design was used with 50 patients who underwent breast MRI at Prof. Dr. I.G.N.G Ngoerah Hospital, Denpasar. ADC values were compared with histopathology for cancer confirmation and surgical reports for staging. At a cut-off of 1.088 × 10⁻³ mm²/s, ADC demonstrated excellent performance in distinguishing cancer from non-cancer (sensitivity 100%, specificity 96%, PPV 96.1%, NPV 100%, LR+ 25, LR- 0.0, accuracy 98%). However, for detecting locally advanced disease (cut-off 0.815 × 10⁻³ mm²/s), performance was lower (sensitivity 61.5%, specificity 75%, accuracy 68%). These results emphasize ADC's reliability in diagnosing breast cancer but suggest limitations in staging, highlighting the need for multimodal imaging and clinical assessment integration to improve accuracy and guide treatment decisions.